2019
DOI: 10.1021/acsomega.8b02459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Ambient Temperature on Emissions and Electric Range of Plug-In Hybrid Electric Vehicles

Abstract: Plug-in hybrid electrical vehicles (PHEVs) are generally considered to be a cleaner alternative to conventional passenger cars. However, there is still very limited information available regarding criteria pollutant emissions from these vehicles. This paper shows, for the first time, the emissions of criteria pollutants, unregulated pollutants, and CO 2 and also electric range from two very different PHEVs, one Euro 6 parallel plug-in hybrid and one range-extended battery electric vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 33 publications
13
13
0
Order By: Relevance
“…Distance-based N 2 O emission factors obtained for modern gasoline LDV (Euro 5 and Euro 6) were in good agreement with those obtained from a US type-approved super ultra-low emission vehicle (SULEV) compliant LDV, whose N 2 O emission were found to be lower than 6 mg/km [3]. N 2 O from the gasoline LDV measured were also found in the same order of magnitude compared to another studies, such as one on plug-in hybrid vehicle [53], and one including new and aged gasoline Tier 2 standard vehicles analyzed at the Environmental Canada and California Air Resources Board between 2001 and 2007 [34]. However, the same study reported average values of 4 and 6 mg/km for diesel vehicles complying with Euro 3 and Euro 4 standards, respectively, thus substantially lower than values reported for Euro 5 and Euro 6 diesel LDV included in the present study.…”
Section: Comparison Of Data With the Literature Valuessupporting
confidence: 84%
“…Distance-based N 2 O emission factors obtained for modern gasoline LDV (Euro 5 and Euro 6) were in good agreement with those obtained from a US type-approved super ultra-low emission vehicle (SULEV) compliant LDV, whose N 2 O emission were found to be lower than 6 mg/km [3]. N 2 O from the gasoline LDV measured were also found in the same order of magnitude compared to another studies, such as one on plug-in hybrid vehicle [53], and one including new and aged gasoline Tier 2 standard vehicles analyzed at the Environmental Canada and California Air Resources Board between 2001 and 2007 [34]. However, the same study reported average values of 4 and 6 mg/km for diesel vehicles complying with Euro 3 and Euro 4 standards, respectively, thus substantially lower than values reported for Euro 5 and Euro 6 diesel LDV included in the present study.…”
Section: Comparison Of Data With the Literature Valuessupporting
confidence: 84%
“…Regarding the non-regulated pollutants, NH3 emissions (27 mg/km) were 2.5 times higher at −7 °C than at 23 °C and N2O (2 mg/km) and NO2 (15 mg/km) did not vary. Emissions of NH3 and N2O were comparable to those reported in a series of studies that investigated emissions of non-regulated pollutants from conventional gasoline, hybrid and plug-in hybrid vehicles at cold ambient temperatures [20,31,36]. NO2 was slightly higher than what was reported for Euro 6b gasoline vehicles, which were below the limit of detection.…”
Section: Modified Cyclessupporting
confidence: 77%
“…Ammonia (NH 3 ) emissions (11 mg/km) from the GPF-equipped GDI vehicle studied were 2 times lower than what has been reported for other Euro 6b GDIs tested at 23 • C [20,29,30] and comparable to what has been reported for a Euro 6b plug-in hybrid GDI (7 ± 1 mg/km) [31]. This suggests that this vehicle with this aftertreatment system do not diverge from the levels of NH 3 emissions currently reported for gasoline vehicles.…”
Section: Cycles At 23-25 • Csupporting
confidence: 62%
See 1 more Smart Citation
“…During this combustion operation NO x and H 2 react and form NH 3 over the TWC increasing the emissions of NH 3 , which is not regulated for light-duty vehicles. As a result, NH 3 is now the dominant reactive nitrogen species emitted by gasoline and LPG vehicles [27,28], including hybrids [29,30]. Moreover, the budget of transport-related NH 3 emissions has been expected to increase as a result of a more intensive use of the SCR systems installed by the most recent diesel vehicles in order to meet the NO x requirements recently introduced with real driving emissions (RDE) procedure [31,32].…”
mentioning
confidence: 99%